#### Answer

$x^{2}+x-12$

#### Work Step by Step

We are given that $f(x)=x^{2}-9$, $g(x)=2x$, and $h(x)=x-3$.
We are asked to find the value of $(f+h)(x)$. We know that $(f+h)(x)=f(x)+h(x)$.
Therefore, $(f+h)(x)=(x^{2}-9)+(x-3)=x^{2}+x-9-3=x^{2}+x-12$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$x^{2}+x-12$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.